LEARNING GUIDANCE USING THE ZOOM APPLICATION TO OVERCOME STUDENT LEARNING OBSTACLES AT SCHOOL - Ture, Mariana Angela; Bili, Anastasia; Wao, Yosephina Payu; Dhajo, Florentina B; Djou, Laurentius Dominicus Gadi (LPPM Universitas Flores, 2025)
Education plays a crucial role in the development of individuals and the nation. The goal of national education is to form quality, faithful, and noble human beings. Information technology has changed the learning landscape, with the internet and interactive multimedia offering easy access and an engaging learning experience. However, challenges remain, such as the traditional lecture method that makes students passive and less motivated. This service explores the use of the Zoom application as a solution to improve the quality of learning at Kelimutu Ende Private Middle School. Zoom, as a video communication platform, enables virtual face-to-face interaction between teachers and students, facilitating effective distance learning. Through training and mentoring, teachers at Kelimutu Ende Private Middle School have utilised Zoom to deliver learning materials, use interactive features, and evaluate student understanding. The results show that the implementation of Zoom has increased students' enthusiasm and interest in learning. They feel more motivated and involved in the learning process. Teachers also feel the benefits in delivering material more clearly and interactively. Thus, the Zoom application has proven to be an effective tool in improving the quality of learning at Kelimutu Ende Private Middle School, helping to achieve national education goals.